A Bibliometric and Visualised Analysis of Proliferative Verrucous Leucoplakia From 2003 to 2023 - Long Zhu; Lijia Ou; Yang Yang; Danwei Zhao; Binjie Liu; Rui Liu; Ousheng Liu; Hui Feng (International Dental Journal)
Background: Proliferative verrucous leucoplakia (PVL) is a rare but slow-growing, aggressive leucoplakia lesion associated with the highest malignant transformation rate in oral potentially malignant disorders (OPMDs). With increasing attention paid to PVL, it is urgent for us to analyse and summarise the publications globally using comprehensive bibliometric studies to help researchers propose possible future research directions and guide them to further conduct relevant studies in the domain. Objectives: The purpose of the study was to evaluate global academic productivity, impact, and collaboration of potentially malignant oral disorder PVL utilising bibliometrics based on annual number of publications, countries and regions, institution, authors, journals, citations and co-occurrences of author keywords over the last 20 years. Methods: This study searched publications pertaining to proliferative verrucous leucoplakia in the Web of Science Core Collection, spanning from 2003 to 2023. Utilizing VOSviewer, R software, Bibliometric online analysis platform, CiteSpace software, and Microsoft Excel, we conducted a bibliometric and visualised analysis of PVL. Results: The quantity of pertinent publications in this research domain displays a fluctuating but overall upward trend. In aggregate, there are 148 articles and 61 reviews, encompassing research contributions from 44 countries, 45 institutions, and involving 831 authors. Among these publications, the USA, Spain, and UK emerged as the predominant contributing nations. Predominantly, articles found their publication venue in “Pathology Research and Practice.” Notably, the author with the highest number of publications and most influence is Warnakulasuriya S. The top 3 keywords include “Proliferative Verrucous Leucoplakia,” “Squamous-Cell Carcinoma,” “Oral Leucoplakia,” and “Potentially Malignant Disorders.” Conclusion: In this investigation, statistical analysis and network visualisation were conducted to reveal the research progress, trends, and trending topics on PVL via a thorough bibliometric analysis. We found that current publications comprise mainly case reports, there is a significant research need to explore the molecular mechanisms, specific diagnostic criteria, and effective management options for PVL. Our work should serve as a key reference and a directional guide for future research in this domain.